Cranky - Tran, Phuc, 1974- (Harper, an imprint of HarperCollins Publishers, 2024)
"Cranky is feeling, well, cranky. But don't ask why. Because you know what doesn't help when you're feeling cranky? Everyone asking you what's wrong! Is there anything that will help? Find out in this irresistible story about big trucks, big feelings, and even bigger friendships"--Front flap of jacket.